Efficient and Error-Free Replication Past a Minor-Groove DNA Adduct by the Sequential Action of Human DNA Polymerases ι and κ - Washington, M. Todd (American Society for Microbiology, 2004)
DNA polymerase ι (Polι) is a member of the Y family of DNA polymerases, which promote replication through DNA lesions. The role of Polι in lesion bypass, however, has remained unclear. Polι is highly unusual in that it incorporates nucleotides opposite different template bases with very different efficiencies and fidelities. Since interactions of DNA polymerases with the DNA minor groove provide for the nearly equivalent efficiencies and fidelities of nucleotide incorporation opposite each of the four template bases, we considered the possibility that Polι differs from other DNA polymerases in not being as sensitive to distortions of the minor groove at the site of the incipient base pair and that this enables it to incorporate nucleotides opposite highly distorting minor-groove DNA adducts. To check the validity of this idea, we examined whether Polι could incorporate nucleotides opposite the γ-HOPdG adduct, which is formed from an initial reaction of acrolein with the N(2) of guanine. We show here that Polι incorporates a C opposite this adduct with nearly the same efficiency as it does opposite a nonadducted template G residue. The subsequent extension step, however, is performed by Polκ, which efficiently extends from the C incorporated opposite the adduct. Based upon these observations, we suggest that an important biological role of Polι and Polκ is to act sequentially to carry out the efficient and accurate bypass of highly distorting minor-groove DNA adducts of the purine bases.